Foot Health and Lower Extremity Function in People With Multiple Sclerosis: A Cross‐Sectional Survey Study - Stolt, Minna; Eränen, Maria; Katajisto, Jouko; Rosio, Riitta (John Wiley & Sons, 2026)
Introduction
Foot health and lower extremity function are important issues for people with multiple sclerosis (MS). However, relatively little is known about foot health among people with MS. The potential association between foot health and lower extremity function in particular has seldom been studied. Therefore, this study aimed to analyse the level of self-reported foot health and lower extremity function in people with MS and to identify possible associating factors.
Methods
A cross-sectional survey study design was applied. The data were collected online April–May 2024 from members of a national patient association with the Self-administered Foot Health Assessment Instrument, the Lower Extremity Functional Scale (LEFS) as well as a background information form. The data were analysed with descriptive and inferential statistics.
Results
The participants (n = 969, response rate 23%) had many foot problems of which dry skin (73%), cold feet (65%), leg cramps (61%), foot pain (59%) and thickened toe nails (51%) were the most common. Participants experienced mild to moderate lower extremity-related functional limitation (mean 51, SD 22, range 0–80). Foot health among people with MS associated with gender, being on sick leave due to foot problems, perceived knowledge levels of foot self-care, and self-evaluated level of foot health. Moreover, weak but significant correlation between foot health and lower extremity function was found, indicating that a poorer foot health was associated with more difficulties in performing lower extremity-related actions.
Conclusion
The results suggest that not only are foot problems among people with MS extremely prevalent, but they also impact functional ability. People with MS could benefit from regular rehabilitative care that includes access to podiatric care. Future research is needed to develop and evaluate strategies to support self-care in lower extremity health among people with MS.